2006
DOI: 10.1038/sj.jhh.1002093
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical implications of the inter-arm blood pressure difference: a systematic review

Abstract: A blood pressure (BP) difference between arms was first reported over 100 years ago. Knowledge of its prevalence and relevance to the accurate measurement of BP remains poor. Current hypertension guidelines do not emphasise it. The objectives of this study were to establish the best estimate of prevalence of the interarm difference (IAD) in the population, to consider its implications for accurate BP measurement and treatment, and to discuss its aetiology and potential as a risk marker for cardiovascular disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
6
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(157 citation statements)
references
References 67 publications
(74 reference statements)
11
128
6
10
Order By: Relevance
“…The sequential method of BP recording was chosen as a pragmatic method of investigation within the consultation; we have addressed the limitations of this method elsewhere. 4 However, the small difference in the magnitude of the absolute BPs between the right and left arms suggests that no systematic bias was introduced by this method, and this is in keeping with data from previously reported large series. 7,[20][21][22] Although there was good correlation of IADs between attendances, this study did not measure changes to the IAD over the follow-up period.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The sequential method of BP recording was chosen as a pragmatic method of investigation within the consultation; we have addressed the limitations of this method elsewhere. 4 However, the small difference in the magnitude of the absolute BPs between the right and left arms suggests that no systematic bias was introduced by this method, and this is in keeping with data from previously reported large series. 7,[20][21][22] Although there was good correlation of IADs between attendances, this study did not measure changes to the IAD over the follow-up period.…”
Section: Discussionsupporting
confidence: 73%
“…Although our prevalence figures of 23% with a sIAD X10 mm Hg and 6% with a dIAD X10 mm Hg are lower than the figures that we and others have reported previously from primary care, 3,7,15,16 they are close to the best estimates we have calculated from the most methodologically robust studies. 4 We had anticipated a higher prevalence of the IAD than we reported previously, as it has been shown to occur more frequently in hypertensive than normotensive populations in selective studies, 4,[17][18][19] but no previous series of hypertensive patients reported from primary care was available to support this contention. The final prevalence figures were lower than those in our interim report 3 on this cohort, but we have previously shown that prevalence will fall with repeated pairs of measurements.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Some studies reported that an increased carotid-the intima-media thickness (IMT) in the left carotid artery [15] [16]. A previous study suggested that the cause of |ΔSBP| ≥10 mm Hg was pathologic rather than physiologic [17]. In addition to anatomical evidence for |ΔSBP| ≥10 mm Hg, aortic dissections, aortitis, infraclavicular arterial occlusion, and arterial embolism may be attributed to a thrombus complicated by atrial fibrillation, congenital coarctation of the aorta, or higher BP in the left arm, compared with the right arm [18] [19].…”
Section: Causes Of |δSbp| ≥10 MM Hg and Sample Size Calculated As Thmentioning
confidence: 99%
“…It seems ludicrous at a time when GPs in particular are being asked to provide more and more evidence of their fitness to work as GPs in the form of extended training, changes to examinations, and reaccreditation, that there is a group of nurses working in the NHS doing very similar work, with similar outcomes, and patient satisfaction, 2 with nothing more mandatory than a registered nurse qualification.…”
Section: Nurse Practitionersmentioning
confidence: 99%